On the stellar content of the open clusters Melotte 105, Hogg 15, pismis 21 and Ruprecht 140 - Piatti, Andres Eduardo (2001)
CCD observations in the B, V and I passbands have been used to generate colour-magnitude diagrams reaching down to V = 19 mag for two slightly characterized (Melotte 105 and Hogg 15) and two almost unstudied (Pismis 21 and Ruprecht 140) open clusters. The sample consists of about 1330 stars observed in fields of about 4'x4'. Our analysis shows that neither Pismis 21 nor Ruprecth 140 are genuine open clusters since no clear main sequences or other meaningful features can be seen in their colour-magnitude diagrams. Melotte 105 and Hogg 15 are open clusters affected by E(B-V) = 0.42 +/- 0.03 and 0.95 +/- 0.05, respectively. Their distances to the Sun have been estimated as 2.2 +/- 0.3 kpc and 2.6 +/- 0.8 kpc, respectively, while the corresponding ages estimated from empirical isochrones fitted to the main sequence cluster sequences are approximately 350 Myr and 300 Myr, respectively. The present data are not consistent with the membership of the WN6 star HDE 311884 to Hogg 15.